1994
DOI: 10.1080/0031383940380308
|View full text |Cite
|
Sign up to set email alerts
|

Some Reflections on Motivating Situations and Situational Teaching

Abstract: Debates about the crisis of school teaching in the Western world have focused more on education as a state of the art and on psychological problems of either teachers or pupils than on situational features which are of importance for teaching and learning situations. In applying K. R. Popper's propensity theory and his idea of situational logic, a preliminary analysis of problem situations is attempted with the aim of identifying biopsychological situational elements in children's preschool life-conditions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Modern brain science research showed that children in rich environments have a higher IQ [33], and situational teaching can meet the needs of students' development from novice learners to autonomous learners. Situational learning helps students maintain interest in class [34][35][36][37][38], feel happy, and increases their motivation [31,39,40]. Real situations create knowledge that is rooted and connected, promoting learners to actively construct it through interaction with the environment [41,42], and improves students' problem-solving ability [27,43].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modern brain science research showed that children in rich environments have a higher IQ [33], and situational teaching can meet the needs of students' development from novice learners to autonomous learners. Situational learning helps students maintain interest in class [34][35][36][37][38], feel happy, and increases their motivation [31,39,40]. Real situations create knowledge that is rooted and connected, promoting learners to actively construct it through interaction with the environment [41,42], and improves students' problem-solving ability [27,43].…”
Section: Literature Reviewmentioning
confidence: 99%